2021
DOI: 10.1016/j.radcr.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous common bile duct stricture mimicking a cholangiocarcinoma: A case report

Abstract: Biliary involvement during abdominal tuberculosis is extremely uncommon and represents a challenging diagnosis that can easily be mistaken for a malignant etiology. We report the case of a 40 years old male who presented with anorexia, chronic abdominal pain, and progressive obstructive jaundice. Abdominal computed tomography demonstrated distal narrowing with wall thickening of the main biliary duct, along with enlarged lymph nodes and signs of portal hypertension. Abdominal magnetic resonance imaging showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…An interesting article by Adil et al reported a similar case of TB mimicking cholangiocarcinoma, however, it was the presence of multiple lymph nodes that favoured the diagnosis of TB in the patient 11. The absence of lymph nodes though not typical of TB does not rule it out.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting article by Adil et al reported a similar case of TB mimicking cholangiocarcinoma, however, it was the presence of multiple lymph nodes that favoured the diagnosis of TB in the patient 11. The absence of lymph nodes though not typical of TB does not rule it out.…”
Section: Discussionmentioning
confidence: 99%
“…Cholangiocarcinoma (CCA) is a malignant tumor originating from the extrahepatic bile duct, including the bile duct from the hilar region to the lower end of the common bile duct [ 1 , 2 ]. Most patients with CCA have jaundice, weight loss, abdominal pain, sometimes accompanied by fever, abdominal mass, and other symptoms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%